Super ring modern circumcision training with free needle injection anesthesia in improving the skills of health workers - Andri Suwarno; Lutfi Aulia Rahman; Nanang Saputro Agung Widodo; Heryyanoor Heryyanoor; Annisa Febriana; Ida Yuliana (Community Empowerment, 2022)
The development of circumcision techniques in the world, including Indonesia, is very rapid. One of them is super ring modern circumcision with free needle injection anesthesia. Efforts to improve the skills of health workers such as doctors and nurses through training are carried out in collaboration with LKP Sunat Modern Indonesia. The methods used are question and answer lectures, demonstrations, FGDs, and the practice of performing circumcision on patients directly with the assistance and supervision of the instructor. The result of this activity is an increase in understanding and skills in performing super ring modern circumcision with free needle injection anesthesia, and producing entrepreneurs in this field.